Assistant Engineer receives Lifelong Learning Professional Award for Part-Time Programme - Siti Nurfarmy, Ibrahim (2022)
KUANTAN, 17 March 2022 – Adhering to the principle of ‘always thinking positively despite various tests’, Kuala Terengganu-born Roszitaida Adzemin, 37, is now able to smile brightly when selected as the recipient of the Lifelong Learning Professional Award – Part-Time Programme at the Universiti Malaysia Pahang (UMP) 15th Convocation Ceremony, which took place at Dewan Jubli Perak Sultan Haji Ahmad Shah, Kuantan.